When pursuing multiple goals, people prioritize the minimally acceptable level over the aspiration level - LEE, Huey Woon (Institutional Knowledge at Singapore Management University, 2017)
When pursuing multiple goals over time, the amount of time (i.e., resources) available affects which goal is pursued: people prioritize (i.e., spend time on) the goal furthest from the aspiration level when there is plenty of time available to attain the aspiration level on the multiple goals but switch to prioritize the goal closest to the aspiration level when the time available starts to run out (e.g., Schmidt, Dolis, & Tolli, 2009). Although the aspiration level is the most commonly examined goal level, other goal levels possessing different psychological meanings (e.g., minimally acceptable or status quo goal levels) also exist. I examined the effect of multiple goal levels (i.e., the minimally acceptable level and the aspiration level) on goal prioritization decisions. I hypothesized that when people were provided with both the minimally acceptable level and the aspiration level, they would prioritize attaining the minimally acceptable level over the aspiration level. Participants (N=316) engaged in a fully within-persons decision-making task where they repeatedly decided which of two goals to allocate their time to. The amount of time available for allocation was systematically varied. Results indicated that people first strived for the minimally acceptable level on one goal. When they attained the minimally acceptable level on that goal, they switched to striving for the minimally acceptable level on the second goal. Only when people attained the minimally acceptable levels for both goals did they strive for the aspiration level (on one of the goals). The only exception is when they had insufficient time to attain both minimally acceptable goal levels; in that case, they focused only on one goal and strived for the aspiration level on that goal. Results imply that when choosing which goal to prioritize, people consider multiple goal levels. Implications of multiple goal levels for goal pursuit, goal revision, and theories of motivation are discussed.